Environmental Health Literacy Regarding Fine Particulate Matter and Related Factors Among Village Health Volunteers in Upper Northern Thailand - Nattapon Pansakun; Warangkana Naksen; Waraporn Boonchieng; Parichat Ong-artborirak; Tippawan Prapamontol (Korean Society for Preventive Medicine, 2024)
Objectives: Fine particulate matter pollution has emerged as a significant life-threatening issue in Thailand. Recognizing the importance of environmental health literacy (EHL) in disease prevention is crucial for protecting public health. This study investigated EHL levels and aimed to identify associated factors among village health volunteers (VHVs) in the upper northern region of Thailand. Methods: A cross-sectional study was conducted to collect data from 710 VHVs using the EHL assessment tool developed by the Department of Health, Thailand. Results: The overall EHL score was moderate (mean, 3.28 out of a possible 5.0), with the highest and lowest domain-specific mean score for the ability to make decisions (3.52) and the ability to access (3.03). Multiple linear regression revealed that the factors associated with EHL score were area of residence (urban areas in Chiang Mai: B=0.254; urban areas in Lampang: B=0.274; and rural areas in Lampang: B=0.250 compared to rural areas in Chiang Mai), higher education levels (senior high school: B=0.212; diploma/high vocational certificate: B=0.350; bachelor's degree or above: B=0.528 compared to elementary school or lower), having annual health checkups compared to not having annual health check-ups (B=0.142), monthly family income (B=0.004), and individuals frequently facing air pollution issues around their residence (B=0.199) compared to those who reported no such issues. Conclusions: The VHVs exhibited moderate EHL associated with residence area, education, health check-ups, family income, and residential air pollution. Considering these factors is vital for enhancing VHVs' EHL through strategic interventions.